Comparison of Traditional Upper Airway Surgery and Upper Airway Stimulation for Obstructive Sleep Apnea. (April 2021) - Huntley, Colin; Boon, Maurits; Tschopp, Samuel; Tschopp, Kurt; Jenks, Carolyn M; Thaler, Erica; Baptista Jardin, Peter; Shah, Janki; Kominsky, Alan; Kezirian, Eric J; Heiser, Clemens; Waxman, Jonathan; et al.
Objective: To compare patients with moderate-severe obstructive sleep apnea (OSA) undergoing traditional single and multilevel sleep surgery to those undergoing upper airway stimulation (UAS). Study Design: Case control study comparing retrospective cohort of patients undergoing traditional sleep surgery to patients undergoing UAS enrolled in the ADHERE registry. Setting: 8 multinational academic medical centers. Subjects and Methods: 233 patients undergoing prior single or multilevel traditional sleep surgery and meeting study inclusion criteria were compared to 465 patients from the ADHERE registry who underwent UAS. We compared preoperative and postoperative demographic, quality of life, and polysomnographic data. We also evaluated treatment response rates. Results: The pre and postoperative apnea hypopnea index (AHI) was 33.5 and 15 in the traditional sleep surgery group and 32 and 10 in the UAS group. The postoperative AHI in the UAS group was significantly lower. The pre and postoperative Epworth sleepiness scores (ESS) were 12 and 6 in both the traditional sleep surgery and UAS groups. Subgroup analysis evaluated those patients undergoing single level palate and multilevel palate and tongue base traditional sleep surgeries. The UAS group had a significantly lower postoperive AHI than both traditional sleep surgery subgroups. The UAS group had a higher percentage of patients reaching surgical success, defined as a postoperative AHI <20 with a 50% reduction from preoperative severity. Conclusion: UAS offers significantly better control of AHI severity than traditional sleep surgery. Quality life improvements were similar between groups.